Effectiveness of didactic strategies in the Blended Learning modality at the Tecnologico Nacional INATEC Matagalpa – Nicaragua - Muñoz Gonzáles, Juana Paula (Revista Científica Estelí, 2023)
The National Model of Technical Education and Vocational Training based on competence of INATEC faces constant challenges to permanently update the offer of Technical Education and Vocational Training, in correspondence to the advances in science, technology and demand of the productive sectors (SITEAL, 2018). Therefore, didactic strategies are of vital importance in the implementation of the new modalities of modern education. The present research was conducted at the National Technological INATEC, in the National Center for Teacher Training in the municipality of Matagalpa, period 2021-2022. The purpose of the study is to strengthen educational quality in continuous improvement through the implementation of innovative strategies in the Blended Learning modality. An observational methodology was used, the level of depth of knowledge is descriptive, the period and sequence of study is transversal, the philosophical approach is mixed, based on a socio-critical paradigm. The sample consisted of 10 teachers and 68 students who demonstrate the effectiveness of the didactic strategies to be implemented in the learning sessions. The results obtained by the teachers in the sense of effectiveness are: Problem-based learning 88.9%, gamification 77.8%, collaborative learning 66.75% thinking-based learning 66.7%, project-based learning 77.8%, flipped classroom 33.3%, design thinking 33.3%, cooperative learning 33.3%.